L-type Amino Acid Transporter 1 Expression Increases in Well-Differentiated but Decreases in Poorly Differentiated Endometrial Endometrioid Adenocarcinoma and Shows an Inverse Correlation With p53 Expression. Issue 4 (1st May 2014) - Watanabe, Jun; Yokoyama, Yoshihito; Futagami, Masayuki; Mizunuma, Hideki; Yoshioka, Haruhiko; Washiya, Kiyotada; Hana, Kiyomi; Endou, Hitoshi; Okayasu, Isao
Abstract : Objectives: The aims of this study were to determine whether the altered L-type amino acid transporter 1 (LAT1) expression is related to clinicopathologic factors, expressions of Ki-67, p53, estrogen receptor, and progesterone receptor and clarify the significance of LAT1 as a prognostic factor and the novel possibility of using it to treat endometrial endometrioid adenocarcinoma. Methods: The LAT1 expression was analyzed immunohistochemically in atrophic (6 cases), secretory phase (6 cases), proliferative phase endometria (6 cases), atypical hyperplasia (6 cases), and endometrioid adenocarcinoma (26 well-differentiated [G1], 17 moderately differentiated, and 11 poorly differentiated [G3] adenocarcinoma patients). Results: The LAT1 expression was observed in the cell membrane. Its expression increased in the atrophic, secretory, and proliferative phases of the endometrium in that order. There was no difference between the proliferative phase endometrium, atypical hyperplasia, and G1 adenocarcinoma. The LAT1 expression in G1 adenocarcinoma was significantly higher than that in G3 adenocarcinoma. The LAT1 expression was inversely correlated with p53 expression but not with those of Ki-67, estrogen receptor, or progesterone receptor. Conclusions: It is suggested that the significance of LAT1 as a prognostic factor is low because LAT expression was low in G3 adenocarcinoma, not correlated with the International Federation of Gynecology and Obstetrics stage and proliferative activity and inversely correlated with p53. The LAT1 inhibitors can be used as anticancer drugs for G1 and moderately differentiated adenocarcinoma that express high LAT1.